2018
DOI: 10.1038/s41467-017-02283-9
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic nanocarrier-induced modulation of PLK1 and miR-34a leads to improved therapeutic response in pancreatic cancer

Abstract: The heterogeneity of pancreatic ductal adenocarcinoma (PDAC) suggests that successful treatment might rely on simultaneous targeting of multiple genes, which can be achieved by RNA interference-based therapeutic strategies. Here we show a potent combination of microRNA and siRNA delivered by an efficient nanocarrier to PDAC tumors. Using proteomic-microRNA profiles and survival data of PDAC patients from TCGA, we found a novel signature for prolonged survival. Accordingly, we used a microRNA-mimic to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 57 publications
2
65
0
Order By: Relevance
“…167 In addition to using miRNAs to enhance anti-tumor effects, another study reported that the combination of miR-34a and polo like kinase 1 (PLK1) siRNA delivered by biodegradable amphiphilic polyglutamate amine polymer nanocarrier (APA) markedly enhanced anti-tumor effects of miR-34a in the treatment of PC. 168 These studies demonstrated potential clinical applications of miR-34a in the treatment of PC.…”
Section: The Role Of Mir-34a In the Treatment Of Pcmentioning
confidence: 88%
“…167 In addition to using miRNAs to enhance anti-tumor effects, another study reported that the combination of miR-34a and polo like kinase 1 (PLK1) siRNA delivered by biodegradable amphiphilic polyglutamate amine polymer nanocarrier (APA) markedly enhanced anti-tumor effects of miR-34a in the treatment of PC. 168 These studies demonstrated potential clinical applications of miR-34a in the treatment of PC.…”
Section: The Role Of Mir-34a In the Treatment Of Pcmentioning
confidence: 88%
“…In this section, the data were extracted by reading the full texts of the eight papers selected. [37][38][39][40][41][42][43][44] They investigated the impact and interaction of some different miRNAs on the expression of the MYC gene in PDAC. The extracted data were collected by two of the authors and were inserted into the extraction form.…”
Section: Data Extractionmentioning
confidence: 99%
“…Moreover, miR-34 has been shown to be downregulated in pancreatic cancer. The overexpression of miR-34 in these cells increases apoptosis and inhibition of autophagy, reducing tumor growth [44]. Another example is the miR Let-7 family, which targets HRAS and HMGA2 as well as participates in the regulation of proliferation and cell cycle.…”
Section: Micrornas and Cancermentioning
confidence: 99%